The Impact of Alcohol Consumption on the Risk of Stroke - A Systematic Review - Jasik-Zawadka, Klaudia; Kujawa, Barbara; Kozłowska, Dominika; Jankowski, Paweł; Dondajewski, Antoni; Musyt, Wiktoria; Rajczyk, Kamil; Grzeczka, Anna-Maria; Dudziński, Szymon (Quality in Sport, 2025)
Introduction: Both ischemic and hemorrhagic stroke are currently among the leading causes of death and disability worldwide. The causes of stroke are diverse and often involve several interconnected factors. Although alcohol consumption is harmful, it remains widespread among people, leading to many negative consequences for the body. Its impact on the risk of stroke varies depending on the amount and frequency of alcohol intake. Aim of the Study: The aim of this article is to highlight the relationship between alcohol consumption and the occurrence of stroke, emphasizing the multifaceted nature of this phenomenon by considering the amount and frequency of intake, the type of alcohol consumed, and drawing attention to the controversies surrounding this topic. Materials and Methods: A comprehensive literature review was conducted using the PubMed, Google Scholar, with particular focus on studies examining both the short- and long-term effects of alcohol consumption on the risk of stroke, considering both direct and indirect impacts arising from various mechanisms. Results and Conclusions: Alcohol consumption affects the risk of developing stroke. High and very high levels of intake are associated with an increased risk, while data regarding low and moderate consumption remain inconclusive, indicating the need for further research on this topic.